Futuristic Composites Behavior, Characterization, and Manufacturing (Materials Horizons: From Nature to Nanomaterials,, 2018)
This book presents a collection of chapters on various aspects of futuristic composite materials, from manufacturing challenges to materials characterization. The book covers the scientific basis of processing and synthesizing futuristic composites, including the prerequisite theoretical background and latest fabrication techniques. The book also discusses industrial applications of composites, such as in aerospace, automotive, and sports equipment. This book will serve as a valuable guide for researchers and professionals working in the area of futuristic lightweight materials.